Bantar Gebang TPST as a garbage processing facility in Bekasi which is now owned by DKI Jakarta has positive and negative effect for social change in Bantar Gebang area. So this study aims to analyze what are the social impacts negatively and positively felt by residents living in the TPST area. For that writer analyze by using social change theory of Selo Soemardjan and seen from scavenger point of view and society in TPST area in Sumur Batu Village that feel impact from TPST. The result of thi - faishal luthfianwar; Budi Setiyono; dzunuanus ghulam manar (Journal of Politic and Government Studies, 2018)
Suitable house is the basic needs of all human beings. However, there are alot of indonesian people has not been able to meet those needs. Based on the PBDT (Integrated Data Base Update) in 2015 carried out by BPS (Central Bureau of Statistics). The number of unsuitable house in Semarang District totaled 39,984 housing units with a priority totalling 30,731 housing units is unsuitable located in the red area (Poverty Area). Based on the data, Semarang District Government conduct the rehabilitation programs of unsuitable house to overcome these problems. The purpose of this study is to describe the implementation of rehabilitation programs for unsuitable house, supporting and restricting factors, and provide an alternative policy or program to increase rehabilitaion programs for unsuitable house.This research used qualitative descriptive method. Descriptive research is problem-solving procedure that examined illustrate a subject or object of research in accordance with the facts as well as about an ongoing process in the field. In obtaining the data, researchers conduct interviews toward Community Empowerment Agency (Bapermades), Development Planning Agency at Sub-National Level (BPPD), and Village Government (Bringin, Nyemoh, Gogodalem, and Sambirejo).The results of this study explain that implementation of rehabilitation programs for unsuitable house in Semarang District has been running well enough. The implementation of the program is compliance with regulation and able to improve the house quality that previously unsuitable to become suitable. The program also encourage low-income communities to build their own suitable homes in accordance with the intent and purpose of the program. In the implementation of the program, there are supporting factors from the recipient or the community in the form of “gotong royong” and also the commitment from stakeholder. In addition there are also obstacle factors in the implementation of the program such as social jealousy, resources, data, infrastructure, natural RTLH, trust, and synergy programs.The suggested recommendations for this study are including the toilets as a component criteria for the rehabilitation, examine the return on the implementation system requires the existence of non-governmental aid receiver, make the database specified and ratified RTLH also updated periodically, invite private party and commercial bank to contribute in overcoming problems RTLH in Semarang, making digital application system for the verification process, networking and data updates, and perform RTLH synergy programs.Keywords: Implementation, Rehabilitation, House